Water Extract Activity of Papaya Leaf as Antibiofilm against Escherichia coli - Livia Rhea Alvita; Syamsul Falah; Novik Nurhidayat (IPB University, 2015)
Biofilms are significant hazards in the food industry. The presence of Escherichia coli biofilms in food industry is potentially causing food spoilage that will shorten the shelf life as well as lead to the spread of disease through food. The purpose of this study is to determine the phytochemical compound of aqueous extract of papaya leaves and to determine its activity on inhibition of cell attachment and growth, and on degradation of the biofilm using Micro-titter Plate Biofilm Assay. The results phytochemical test showed that papaya leave extract contains alkaloid, tanin, flavonoid, and steroid and have anti-biofilm activity. Papaya leave extract with highest activity caused biofilm degradation of 48,99%. The optimum temperature of biofilm degradation (>52,5%) by papaya leaves extract was around 35oC - 40oC. The optimum contact time and extract concentration were 57-60 minutes and 75-100%, respectively.